VD_FINDINFO Faillite / 2012 / 47 vom 31. August 2012 - VD Tribunal cantonal (2012)
PROCÉDURE DE FAILLITE, INSOLVABILITÉ, RESTITUTION DU DÉLAI, PRINCIPE DE LA BONNE FOI | 5 al. 3 Cst., 174 LP, 33 al. 4 LP